No evidence of widespread mechanical pressure hyperalgesia after experimentally induced central sensitization through skin nociceptors. (November 2018) - Cayrol, Timothée; Pitance, Laurent; Roussel, Nathalie; Mouraux, André; van den Broeke, Emanuel N.
Abstract: Introduction: An increasing number of clinical studies involving a range of chronic pain conditions report widespread mechanical pressure pain hypersensitivity, which is commonly interpreted as resulting from central sensitization (CS). Secondary hyperalgesia (increased pinprick sensitivity surrounding the site of injury) is considered to be a manifestation of CS. However, it has not been rigorously tested whether CS induced by peripheral nociceptive input involves widespread mechanical pressure pain hypersensitivity. Objectives: The aim of this study was to assess whether high-frequency electrical stimulation (HFS), which induces a robust secondary hyperalgesia, also induces a widespread decrease of pressure pain thresholds (PPTs). Methods: We measured PPTs bilaterally on the temples (temporalis muscles), on the legs (tibialis anterior muscles), and on the ventral forearm (flexor carpi radialis muscles) before, 20 minutes after, and 45 minutes after applying HFS on the ventral forearm of sixteen healthy young volunteers. To evaluate the presence of secondary hyperalgesia, mechanical pinprick sensitivity was assessed on the skin surrounding the site where HFS was applied and also on the contralateral arm. Results: HFS induced a significant increase in mechanical pinprick sensitivity on the HFS-treated arm. However, HFS did not decrease PPTs neither in the area of increased pinprick sensitivity nor at more distant sites. Conclusion: This study provides no evidence for the hypothesis that CS, induced after intense activation of skin nociceptors, involves a widespread decrease of PPTs. Abstract : High-frequency stimulation of the skin induces secondary pinprick hyperalgesia but does not affect pressure pain thresholds either locally or at more distant body sites.